Vocal Turn-Taking Between Mothers and Their Children With Cochlear Implants. Issue 2 (March 2020) - Kondaurova, Maria V.; Smith, Nicholas A.; Zheng, Qi; Reed, Jessa; Fagan, Mary K.
Abstract : Objectives: The primary objective of the study was to examine the occurrence and temporal structure of vocal turn-taking during spontaneous interactions between mothers and their children with cochlear implants (CI) over the first year after cochlear implantation as compared with interactions between mothers and children with normal hearing (NH). Design: Mothers' unstructured play sessions with children with CI (n = 12) were recorded at 2 time points, 3 months (mean age 18.3 months) and 9 months (mean age 27.5 months) post-CI. A separate control group of mothers with age-matched hearing children (n = 12) was recorded at the same 2 time points. Five types of events were coded: mother and child vocalizations, vocalizations including speech overlap, and between- and within-speaker pauses. We analyzed the proportion of child and mother vocalizations involved in turn-taking, the temporal structure of turn-taking, and the temporal reciprocity of turn-taking using proportions of simultaneous speech and the duration of between- and within-speaker pauses. Results: The CI group produced a significantly smaller proportion of vocalizations in turn-taking than the NH group at the first session; however, CI children's proportion of vocalizations in turn-taking increased over time. There was a significantly larger proportion of simultaneous speech in the CI compared with the NH group at the first session. The CI group produced longer between-speaker pauses as compared with those in the NH group at the first session with mothers decreasing the duration of between-speaker pauses over time. NH infants and mothers in both groups produced longer within- than between-speaker pauses but CI infants demonstrated the opposite pattern. In addition, the duration of mothers' between-speaker pauses (CI and NH) was predicted by the duration of the infants' between-speaker pauses. Conclusions: Vocal turn-taking and timing in both members of the dyad, the mother and infant, were sensitive to the experiential effects of child hearing loss and remediation with CI. Child hearing status affected dyad-specific coordination in the timing of responses between mothers and their children. Abstract : Supplemental Digital Content is available in the text.